Cyber Physical System vs Learning Factory: Perspective of industry 4.0-based curriculum development. Issue 3 (March 2021) - Widiaty, I; Ana, A; Abdullah, A G; Karyono, T; Suciati, S; Mubaroq, S R; Martawijaya, D H
Abstract: The purpose of this study is to analyze the co-occurrence network of two main keywords in relation to the development of industry 4.0-based curriculum in vocational education. The research method used is bibliometric analysis which can produce information about the most appeared keywords in relation to the main keywords used as input analysis. The search results illustrate that some appeared keywords related to the keywords Cyber Physical System and Learning Factory are then selected into the five highest ranks. The keywords are learning factory which appear twice, industrial revolution 4.0, learning factories, and production system.